Future Scenarios for the Development of Slow Fashion Collection: Brisa Slow Fashion case study (ModaPalavra e-periódico, 2018)
This article brings, as a starter, future scenarios for design insights into sustainable development.For this, elements of the feminine fashion brand BrisaSlow Fashionand its collection development were used.Issues of sustainable trends and megatrends were drawn, as well as the development of fashion,eco-friendly from its idealization to the end of the product life cycle.Outlined by a qualitative exploratory research, the article is based on the case study ofthe brand previously mentioned. The main objective is to develop possibilities of brand action inpossible scenarios in the time span between 5 and 15 years.
Keywords: slow fashion; sustainable fashion collection; future scenarios